Hurricane disturbance results in positive effects on tropical stream meiofauna abundance and richness - Josué Santiago-Vera; Alonso Ramírez (PLoS ONE, 2026)
Hurricanes are major natural disturbances that significantly influence tropical ecosystems. While most research focuses on large-bodied organisms, understanding the impact of hurricanes on small-bodied biota, such as meiofauna, is crucial, especially as climate change models predict more frequent and intense storms. Puerto Rico offers a unique setting to study these effects, as hurricanes and tropical storms are frequent. This research examined the short- (Post-Hurricane A) and medium-term (Post-Hurricane B) impacts of Hurricanes Irma and María (September 2017) on stream meiofaunal communities in a tropical stream in the Luquillo Experimental Forest. Twelve samples were collected monthly from pools across two stream reaches for eight months before and after the hurricanes. Environmental variables, such as discharge, sediment composition, and biotic data, were recorded. Meiofauna were identified to the lowest possible taxonomic level and categorized by phyla and feeding groups. Results showed a significant increase in both richness and abundance of meiofauna following the hurricanes. Richness and abundance peaked during Post-Hurricane A and declined slightly during Post-Hurricane B. This trend was linked to an increase in coarse particulate organic matter, potentially the result of defoliation and debris from hurricane damage of riparian forest. Community structure analyses revealed significant differences between pre- and post-hurricane periods. Variables such as stream discharge, macroinvertebrate presence, sediment size, and shrimp abundance were all influenced by hurricane impacts and correlated with changes in meiofaunal communities. During Post-Hurricane A, models explaining meiofaunal variation involved variables associated with ecosystem disturbance. In contrast, Post-Hurricane B models were simpler, suggesting a level of ecological stabilization. These findings suggest that hurricanes influence meiofaunal communities, but that these organisms are likely benefiting from hurricane disturbance. Given expected increases in hurricane activity due to climate change, hurricanes may play a long-term role in shaping the structure and function of tropical stream communities, in particular for small-body size organisms.